2018
DOI: 10.1136/bmjopen-2018-023772
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula oxygen therapy alone or with non-invasive ventilation during the weaning period after extubation in ICU: the prospective randomised controlled HIGH-WEAN protocol

Abstract: IntroductionRecent practice guidelines suggest applying non-invasive ventilation (NIV) to prevent postextubation respiratory failure in patients at high risk of extubation failure in intensive care unit (ICU). However, such prophylactic NIV has been only a conditional recommendation given the low certainty of evidence. Likewise, high-flow nasal cannula (HFNC) oxygen therapy has been shown to reduce reintubation rates as compared with standard oxygen and to be as efficient as NIV in patients at high risk. Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Two multicenter prospective randomized trials have demonstrated that HFNC could be better than COT [33] and not inferior to NIV [34] to prevent reintubation and post-extubation ARF in low- and high-risk patients, respectively. Results of the ongoing “High-Wean” trial comparing HFNC alone or with NIV in the post-extubation period for high-risk patients should give further evidence in this indication [35].…”
Section: Discussionmentioning
confidence: 99%
“…Two multicenter prospective randomized trials have demonstrated that HFNC could be better than COT [33] and not inferior to NIV [34] to prevent reintubation and post-extubation ARF in low- and high-risk patients, respectively. Results of the ongoing “High-Wean” trial comparing HFNC alone or with NIV in the post-extubation period for high-risk patients should give further evidence in this indication [35].…”
Section: Discussionmentioning
confidence: 99%
“…After extubation, prophylactic use of non-invasive ventilation alternating with high-flow nasal oxygen between non-invasive ventilation sessions will be recommended in all patients for at least 48 hours according to the results of our previous study. 13 14…”
Section: Duration Of Treatment and Strategy Of Weaning And Extubationmentioning
confidence: 99%